2019
DOI: 10.4314/rejhs.v7i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and psychological morbidity among physicians in southwest Nigeria

Abstract: The role of the physician has increasingly become more expansive, and demanding. These demanding schedules have played a heavy toll on sleep patterns and increased psychological stress. The objective of the study was to assess sleep quality and psychological morbidity among Physicians. Method: A cross-sectional survey of 95 voluntary consenting physicians from different specialties during a 2-day conference. We administered Pittsburgh Sleep Quality Index, and General Health Questionnaire-12. Results; About 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
2
4
Order By: Relevance
“…In the same vein, as many as six in every ten participants reported sleep problems. This is significantly higher than the prevalence of sleep problems (36.4%) reported in physicians in a local study using the same instrument ( Ogunsemi et al 2019 ). About eight in every ten participants reported difficulty in the aspects of sleep latency and other disturbances, while seven in ten participants had daytime dysfunction and difficulties with sleep duration.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…In the same vein, as many as six in every ten participants reported sleep problems. This is significantly higher than the prevalence of sleep problems (36.4%) reported in physicians in a local study using the same instrument ( Ogunsemi et al 2019 ). About eight in every ten participants reported difficulty in the aspects of sleep latency and other disturbances, while seven in ten participants had daytime dysfunction and difficulties with sleep duration.…”
Section: Discussioncontrasting
confidence: 64%
“…The rate of psychological distress in the present study is several folds higher than the rates previously reported in the general population in similar contexts ( Erinfolami et al 2016 ; Gureje et al 2006 ). This study rate is also moderately higher than the rates previously reported in healthcare workers, 17.2% ( Obadeji et al 2018 ); doctors, 14.9% and 13.6% ( Issa et al, 2014 ; Ogunsemi et al 2019 ); and company executives, 14.2% in similar contexts using the same screening tool. While the rates of psychological distress in this study is moderately highly, it is conceivable that this estimate of psychological distress in healthcare workers may be conservative given the pervasive reluctance to disclose mental health problems due to stigmatization ( Knaak et al 2017 ; Yussuf and Balogun, 2006 ).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The prevalence of poor sleep quality in this study was 50.2% which is significantly higher than 25.7% reported among the general population in Nigeria by Ogunsemi et al 26. The finding of this study suggests that CKD is associated with poor sleep quality.…”
Section: Discussioncontrasting
confidence: 61%